Zastosowanie modeli wyceny aktywów CAPM, market timing i DLM do oceny inwestycji w spółki innowacyjne - Panek, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The aim of this article is to verify whether investment innovation managers, due to their specificity, should in particular have the ability to sense short-term trends and how this affects the effectiveness and risk of such investments. Empirical research was based on the use of asset valuation models of the classic CAPM, MT (market timing) model, and DLM (dynamic models with distributed delays), the parameters of which were estimated using the Classical Least Squares Methods, based on logarithmic rates of return of companies listed on the WSE in the period from 1st February 2015 to 2nd February 2020. The significantly negative value of the MNK — the estimator of parameter of the MT model, means that managers do not have the ability to sense short-term changes in the market regardless of the sector in which they operate. Furthermore, the impact of delays on market rates of return has been observed. The presented results may constitute recommendations for managers in terms of valuation of MT’s assets and skills and their impact on the effectiveness and risk of innovative investments.
Keywords: CAPM; market timing; dynamic models; innovations